Results of surgical treatment of varicocele in the Department of Urology of Municipal Polyclinic No. 195 (Branch No. 2) - A. R. Gevorkyan; A. Yu. Avakyan; M. D. Pavlyuk; I. S. Pinchuk (Андрология и генитальная хирургия, 2015)
Results of surgical treatment of varicocele of 73 patients in the out-patient ward of the Department of Urology of Municipal Polyclinic No. 195(Branch No. 2) were analyzed within the scope of this study. The authors came to the conclusion that surgical treatment of varicocele with Marmar’s method is an efficient method of therapy. Microsurgical subinguinal varicocelectomy can be performed in the out-patient ward and significantly improves the indicators of the spermogram when monitored in 6 months as well as increases the frequency of spontaneous pregnancies.